Interconnections between Eurozone and US Booms and Busts using a Bayesian Panel Markov-Switching VAR Mode - Monica Billio; Roberto Casarin; Francesco Ravazzolo; Herman K. van Dijk (Tinbergen Institute, 2015)
Interconnections between Eurozone and United States booms and busts and among major Eurozone economies are analyzed using a Panel Markov-Switching VAR model. The model accommodates changes in low and high data frequencies and incorporates endogenous time-varying transition matrices of country-specific Markov chains. These country-specific Markov chains depend on their own past history and the history of other chains, thus allowing for interconnections between cycles, and an endogenous common Eurozone cycle is derived by aggregating the country-specific cycles. The model is estimated using a simulation based Bayesian approach in which an efficient multi-move sampling algorithm is defined to draw time-varying Markov-switching chains. Using industrial production growth and credit spread data for all countries, several empirical results have emerged. Recession, slow gro wth and expansion are empirically identified as three regimes with slow growth becoming persistent in the Eurozone in recent years different from the US. The Eurozone and the US regimes appear not fully synchronized, with evidence of more recessions in the Eurozone. Second, turning point analysis indicates larger synchronization at the beginning of the Great Financial Crisis: this shock affects the US first, leading the Eurozone cycle, and spreads then rapidly among these economies. Third, amplification effects influence recession probabilities for Eurozone countries when shocks occur. The evidence is different for the US where this reinforcement does not exist. In recent years there are more imbalances among regimes in Eurozone countries. Fourth, a credit shock results in substantial negative industrial production growth for several months in Germany, Spain and the US.
Keywords: C11; C15; C53; E37; 330; Bayesian Modelling; Panel VAR; Markov-switching; International Business Cycles; Interaction mechanisms